Children Prioritize Humans Over Animals Less Than Adults Do. (January 2021) - Wilks, Matti; Caviola, Lucius; Kahane, Guy; Bloom, Paul
Is the tendency to morally prioritize humans over animals weaker in children than adults? In two preregistered studies (total N = 622), 5- to 9-year-old children and adults were presented with moral dilemmas pitting varying numbers of humans against varying numbers of either dogs or pigs and were asked who should be saved. In both studies, children had a weaker tendency than adults to prioritize humans over animals. They often chose to save multiple dogs over one human, and many valued the life of a dog as much as the life of a human. Although they valued pigs less, the majority still prioritized 10 pigs over one human. By contrast, almost all adults chose to save one human over even 100 dogs or pigs. Our findings suggest that the common view that humans are far more morally important than animals appears late in development and is likely socially acquired.